Currency substitution : empirical evidence on its significance - Heimonen, Kari (1996)
This study evaluates the issue of currency substitution. Particular interest is focused on impacts on the demand for money and thus on the autonomy of monetary policy in various economies. The introduction discusses the concept of currency substitution and the determinants of the demand for parallel currency together with the models of money demand and the potential consequences of currency substitution. The survey section classifies currency substitution studies on the basis of the underlying theoretical model and the countries studied. Various different theoretical standpoints are reviewed and discussed. Currency substitution is shown to have been a subject of active research and that inferences as to its significance have remained rather independent of the method of estimation or underlying theoretical model employed. The study estimates cointegration and error correction models for money demand in various economies, applying different theories addressing the different role of monies in the countries under scrutiny. The following results were obtained: US money demand is significantly affected by currency substitution in the group of industrialized countries as well as in the Western Hemisphere countries. This points to the significant role of the USD as a international vehicle currency and as a store of value. Second, estimated hyperinflation models indicate that currency substitution is a significant phenomenon in a single country: Argentina. The impacts of currency substitution on the Western Hemisphere country aggregate were in turn, much less important. Third, the demand for narrow money in the Finnish exchange rate system has remained rather independent of currency substitution even though the demand equations for foreign currency deposits clearly show significant currency substitution effects. To summarize, according to the present study, currency substitution is a significant monetary phenomenon in a world of interdependent nations. Accordingly, it should be considered as an option both in models of money demand and in evaluations of monetary policy as well.